Identification of 13 Key Genes Correlated With Progression and Prognosis in Hepatocellular Carcinoma by Weighted Gene Co-expression Network Analysis - Gu, Yang; Li, Jun; Guo, Deliang; Chen, Baiyang; Liu, Pengpeng; Xiao, Yusha; Yang, Kang; Liu, Zhisu; Liu, Quanyan (Frontiers in Genetics, 2020)
Hepatocellular carcinoma (HCC) remains hard to be diagnosed early and cure due to lack of accurate biomarkers and effective treatments. Hence, it is necessary to explore the tumorigenesis and tumor progression of HCC to discover new biomarkers for clinical treatment. We performed weighted correlation network analysis (WGCNA) to explore huh genes which have high correlation with clinical information. In this study, we found 13 huh genes (GTSE1, PLK1, NCAPH, SKA3, LMNB2, SPC25, HJURP, DEPDC1B, CDCA4, UBE2C, LMNB1, PRR11, SNRPD2) which have high correlation with histologic grade in HCC by analyzing HCC data in TCGA database. Meanwhile, these 13 huh genes expressed differently significance between tumor and non-tumor tissues. We downloaded GES6764 which contains corresponding information to validate these 13 huh genes expression. At the same time, we performed quantitative real-time PCR to validate these 13 huh genes between high and low histologic grade. The overall survival and disease-free survival information showed high expression of these 13 huh genes lead to poor prognosis. We also explored mutation and methylation information about these 13 huh genes for further study.